Determinants on green purchasing behavior of generation Y: Empirical evidence in Can Tho city - My Tran Ngo; Thi Kim Thanh Bui; Buu Hau Tran (CTU Journal of Innovation and Sustainable Development)
This study aims to analyze the determinants of green purchasing behavior of Generation Y in Can Tho city based on the survey data from 180 consumers. The results estimated by PLS - SEM show that concern for the environment has the highest impact on green purchasing intention, followed by green price sensitivity and perceived green behavior control. Besides, the evidence indicates that green purchasing intention has a positive effect on the green purchasing behavior of millennials. Based on the research results, several managerial implications have been proposed for businesses in the industry. These include the need to expand selling locations and distribution channels to increase the convenience of finding green products; organizing environmental awareness campaigns in collaboration with government agencies; developing product pricing strategies that reflect the product's value and consumer benefits; and enhancing consumer intentions by implementing communication campaigns that highlight the information and benefits of green products.